Tipologia das relações sociais de Schütz e a ética da alteridade: a experiência urbana do jornal “a verdade rua e crua” - LEÃO, Bianca Conde (Universidade Federal do Pará, 2021)
First published in November 2015, A Verdade Rua e Crua or The Naked Truth of Homelessness is a newspaper exclusively written and produced by homeless individuals in the metropolitan region of Belém. The publication features articles inspired by life on the streets. What is the power of these wandering narratives (JACQUES, 2012)? This question inspired this master’s thesis. We propose to observe the intersubjective social practices of these homeless journalists and compare our reports to the productions of meaning that are revealed through this experience. To accomplish this, we used the typology of social relations by Schütz (1979; 2012) in order to systematize the reports of experiences obtained through printed materials and semi-structured interviews by some of the project's members. We also propose a dialogue with Lévinas' (1980) ethics of otherness as a cross-sectional basis to raise the hypothesis that the newspaper works as a mirror that can reveal the Face of the Other, a Face that is understood as a path to the exercise of the ethics of otherness. As a methodological procedure, in addition to in-depth semi-structured interviews, we use participant observation, since the author is a volunteer for the project, and content analysis of the texts of the newspaper's copies, in the hope of making a critical interpretation of this homeless initiative in the city. From the appearance of this Face, the paradox of proximity and distance between Same and Other emerges, in which an apparent contradiction is created between Shütz’s intersubjectivity and Levinas’ idea of infinite distance which forbids a reduction to sameness. However, it is through the crossing of this Other that is, at the same time, different and similar to the Same, that the places of each one in everyday life are rethought. In the face of these mirror newspapers, the exercise of the ethics of otherness is revealed, since the recognition of the Other's differences does not exempt the Same from its responsibility towards him, because what is common to all human beings is not lost even in situations of extreme vulnerability.